2022
DOI: 10.1177/15593258221074936
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera Chemical Constituents’ In Vitro Antioxidant Potential and Their Response on Spermatozoa Parameters

Abstract: Background: Phytomedicine is becoming more acceptable as an alternative medicinal approach in the modern era. Objectives: The current study examined the antioxidant capacity and in vitro response of phytochemical constituents of  Withania somnifera (Ashwagandha) on standard parameters of healthy volunteer semen. Methods: The phytochemicals and their pharmacological response in a hydroethanolic (30:70 v/v) extract of  W.  somnifera roots were determined using standard protocols. Results: The constituents inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Order Solanales CHEMICAL CONSTITUENTS [36][37][38][39][40] Ashwagandha's acylsterylglucosides and sitoindosides have anti-stress properties. It has been demonstrated that active components of ashwagandha, such as sitoindosides VII-X and Withaferin-A, have strong anti-stress action against acute forms of experimental stress.…”
Section: Class Magnoliopsidamentioning
confidence: 99%
“…Order Solanales CHEMICAL CONSTITUENTS [36][37][38][39][40] Ashwagandha's acylsterylglucosides and sitoindosides have anti-stress properties. It has been demonstrated that active components of ashwagandha, such as sitoindosides VII-X and Withaferin-A, have strong anti-stress action against acute forms of experimental stress.…”
Section: Class Magnoliopsidamentioning
confidence: 99%
“…These aforementioned characteristics make spermatozoa a general and ideal cell model to test in vitro many compounds at different concentrations related and unrelated to the reproductive field (Figure 3). Indeed, many antioxidants [85][86][87][88][89][90][91] have been tested using this model. In addition, spermatozoa have been used as an in vitro monitor of toxicity due to many compounds including natural substances that have potential contraceptive activity; thus, this research has aimed to identify promising products that could be used as vaginal contraceptive agents [92][93][94][95].…”
Section: Human Spermatozoa As a Model For In Vitro Studiesmentioning
confidence: 99%
“…Antioxidative properties of Ashwagandha have been proved in numerous studies before. Ashwagandha's antioxidant potential is due to phytochemical constituents such as flavonoids and phenolic compounds [56]. It has been suggested that reactive oxygen species may contribute to infertility in a variety of ways, for example by interfering with spermatogenesis or sperm-ovum mating [50].…”
Section: Ashwagandha's Impact On the Reproductive Systemmentioning
confidence: 99%
“…Another study investigated the antioxidant capacity and in vitro response of phytochemical constituents of W. somnifera on standard parameters of semen from healthy volunteers [56]. Incubation of semen with W. somnifera extracts improved sperm motility and preserved sperm viability for a longer period than the control.…”
Section: Ashwagandha's Impact On the Reproductive Systemmentioning
confidence: 99%